KEBIJAKAN DEVIDEN DALAM MEMEDIASI FAKTOR FAKTOR KEUANGAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI TAHUN 2018-2021 - Indriyana, Sofi; Wiryaningtyas, Dwi Perwitasari; Ariyantiningsih, Febri (Fakultas Ekonomi dan Bisnis, 2023)
Food and beverage companies play an essential role in economic growth. The food and beverage sector is a sector that the government prioritizes to encourage industry to boost the national economy. One of the fastest-growing industries is the food and beverage industry. Food and beverage companies play an important role, namely, meeting customer needs. This study analyses and examines the effect of Return on equity, Current Ratio, and Total Asset Turnover on company value through Dividend Policy in companies. Company value through Dividend Policy in food and beverage companies listed on the IDX in the 2018-2021 period. This research is quantitative research. The population in this study were all food and beverage companies listed on the IDX during the 2018-2021 period, namely 21 companies. The sampling technique in this study used purposive sampling. This study's data analysis and hypothesis testing used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application show that Return on equity has a positive but insignificant effect on Dividend Policy, Current Ratio has a negative but insignificant effect on Dividend Policy, Total Asset Turnover has a negative but significant effect on Dividend Policy, Return on equity has a positive but insignificant effect on Company Value, Current Ratio has a positive but insignificant effect on Company Value, and Dividend Policy has a positive but insignificant effect on Company Value. Current Ratio has a positive but insignificant effect on Company Value, Total Asset Turnover has a positive but insignificant effect on Company Value, and Dividend Policy has a positive but insignificant effect on Company Value. The results of the indirect effect hypothesis test show that the variable Return on Equity on Company Value through Dividend Policy has a positive but insignificant effect, the Current Ratio on Company Value through Dividend Policy has a negative but insignificant effect, and Total Asset Turnover on Company Value through Dividend Policy has a negative but insignificant effect.